Jean-Baptiste de Sénac’s (1693-1770) Important Work on Cardiology and Valvular Disorders - Karamanou, Marianna; Tsoucalas, Gregory; Gialafos, Elias; A. Vrachatis, Dimitris; Androutsos, George; Poulakou-Rebelakou, Effie (Current Pharmaceutical Design, 2016)
In the 18th century clinical cardiology was based on pulse examination and auscultation by placing the ear directly on the patient’s chest, while diagnosis of heart diseases was done in postmortem examination. In 1749, Jean-Baptiste de Sénac, physician of King Louis XV, published his work on the heart Traité de la structure du coeur, de son action et de ses maladies. It was the result of years of anatomical and physiological study, in an attempt to illuminate heart and its functions. Sénac recognized among several heart disorders, aortic regurgitation, mitral calcification, and mitral regurgitation. His work remained a landmark in valvular pathology and cardiology until the early 19th century.
Keywords: 18th century history of medicine